Pengembangan Media Pembelajaran Berbentuk Kartu Domino pada Pembelajaran Matematika Materi Perkalian Siswa Kelas III Sekolah Dasar - Nora Nasution (LP3M KH Yazid Karimullah Institute, 2023)
This study aims to evaluate the validity and practicality of mathematics learning media in the form of domino cards on multiplication material. The research method used is Research and Development with ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation. The study will be conducted at SD Swasta Supriyadi Medan for third grade students. In order to collect data, research instruments are used such as expert validation, teacher questionnaires, and students. The results of the study explained that the learning media produced receIIIed a very good assessment in terms of validity and practicality. It appears from students' responses, the learning media used is considered